Density and Distribution of False Smut Balls on Infected Rice Panicles - Nessa, B; Salam, MU; Haque, AHMM; Biswas, JK; Jahan, QSA; Khan, MAI; Bhuiyan, MR; Ara, A; Munir, MR; Galloway, J; et al. (Bangladesh Rice Journal, 2017)
Rice false smut (RFSm), considered as a minor importance, has become a serious disease in many rice growing areas of Bangladesh and other parts of the world. Many aspects of its epidemiology still remained unclear, notable the life cycle of RFSm pathogen, its infection site and the smut ball formation on infected panicles. Present research was undertaken to investigate the density and distribution of false smut balls on infected rice panicles aiding to understand on how severe the disease can be in a rice-ecosystem, on which position the smut balls form on infected panicles and likely yield reduction from such disease severity. This study included field observation of natural RFSm infection during 2014, 2015 and 2016, and simulated infection during 2015 in T. Aman rice in the experimental farm of the Bangladesh Rice Research Institute (BRRI), Gazipur, Bangladesh. While the number of smut balls reached as many as 136 (recorded in one panicle in 2015), the study shows there was 81, 54 and 30% probability that maximum of nine, three and only one smut ball would form, respectively. With the scenarios of density of smut ball formation in the study area, the yield loss was estimated as 0.15% for each 1% incidence level. The level of smut ball density varied between years; this severity was most likely influenced by low daily minimum temperature. In the natural observation 34.4, 53.9 and 11.7% of the smut balls were located at the base, mid and apex part of the infected panicles, respectively. When compared the balls of these three positions in relation to potential grain number, the proportion accounted for the base and mid remained almost similar, whereas the proportion in the apex was much lower. It is concluded that false smut balls predominantly form on the lower half of the infected rice panicles. Bangladesh Rice j. 2016, 20(2): 73-79